Entrepreneurship Of Poultry Farmers And Its Determinents - Ghasura, R.S.; Quazi, J.; Sheikh, A.S.; Aswar, B.K.; Charan, Rohit; Patel, A.C. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The present study was conducted by Ex-post facto research design. Fourteen independent variables, relevant to study were included. Coefficient correlation of adoption with independent variables revealed that out of the 14 independent variables tried 9 were positively and significantly correlated (P<0.01, P<0.05) with the extent of knowledge of improved poultry management practices. The remaining five variables viz., age, caste, organizational participation, occupation, annual income were found to be non-significantly correlated.